The substance and form of Islamic Finance instruments: an accounting perspective. Issue 6 (4th August 2021) - Ebrahim, Ahmed; Abdelfattah, Tarek
Abstract : Purpose: This study aims to critically analyze the fundamentals of the current major Islamic Finance (IF) instruments and contracts in light of both the foundations of IF and the concept of substance over form in the accounting conceptual framework. Such analysis is believed to be necessarily for the IF institutions to provide better and more genuine service to their customers. Design/methodology/approach: To achieve the study purpose, the methodology is based on theoretical analysis and analytical review of the major IF contracts. Findings: The IF industry needs to focus on the economic substance of the products offered to their clients. In developing and promoting their products, IF institutions need to focus on the ultimate and substantial goals of Islamic Sharia rather than re-packaging existing conventional products under different arrangements and formats to make them appear as Sharia-compliant to their clients. Both religious scholars and IF professionals need to engage in much deeper analysis and understanding of the substantial design of IF instruments and the concept of usury in modern economy. Research limitations/implications: This paper does not intend to develop a comprehensive framework for the design of IF instruments to meet the economic substance and ultimate goals of IF principles or measure such economic substance. However, that is definitely a subject for further research. Originality/value: By applying concepts like substance over form from other business fields such as the accounting theoretical framework to the IF instruments and contracts, we should gain better understanding and practical implications of these instruments and figure out ways to improve their design to be more consistent with and better serve the ultimate goals of the Islamic Sharia.